European social dialogue and transnational framework agreements as a response to the crisis? - Schömann, Isabelle; Clauwaert, Stefan (Brussels, 2011)
"This Policy Brief attempts to overcome the knowledge gap about how European social partners or workers’ representatives have tried to contribute to facing the challenges and mitigating the (negative) implications of the crisis."